1999
DOI: 10.1007/bf02561612
|View full text |Cite
|
Sign up to set email alerts
|

A new technology of microdispersed silver in polyurethane induces antimicrobial activity in central venous catheters

Abstract: Metal ions or metal ions in complexes or compounds have been used for centuries to disinfect fluids, solids and tissues. The biocidal effect of silver, with its broad spectrum of activity including bacterial, fungal and viral agents, is particularly well known and the term "oligodynamic activity" was coined for this phenomenon. Silver ions have an affinity to sulfhydryl groups in enzyme systems of the cell wall, through which they interfere with the transmembranous energy transfer and electron transport of bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
116
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(121 citation statements)
references
References 30 publications
1
116
0
4
Order By: Relevance
“…It is also known to interfere with the trans-membrane electron transport, block respiratory chain at the cytochromes and cause metabolic flux inducing a proton leakage through the bacterial cell wall (Kim et al 1998;Klasen 2006). In comparison to other metals with antimicrobial properties, silver has the most effective antibacterial action and the least toxicity to animal cells (Guggenbichler et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…It is also known to interfere with the trans-membrane electron transport, block respiratory chain at the cytochromes and cause metabolic flux inducing a proton leakage through the bacterial cell wall (Kim et al 1998;Klasen 2006). In comparison to other metals with antimicrobial properties, silver has the most effective antibacterial action and the least toxicity to animal cells (Guggenbichler et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the presence of thick peptidoglycan layer in case of Gram-positive strains, which hinders the nanoparticle entry (Sondi and SalopekSondi 2004;Nabil et al 2000). But, here the positively charged capping of the polyamines might be valuable for binding with the teichoic acid groups and also the other negatively charged moieties present there, thus helping in the entry of nanoparticles (Guggenbichler et al 1999).…”
Section: Minimum Inhibitory Concentrationmentioning
confidence: 99%
“…Antimicrobial activity of nanoparticles are well known, of all the nanoparticles, silver nanoparticles have been described as the one with the highest level of toxicity for microorganisms and lowest toxicity for animal cells. 10 The researcher reported that the plant extract assists synthesized AgNPs have recently appeared as new antimicrobial agents due to their high surface area to volume ration and unique chemical and physical properties. 11,12 The antibacterial activity AgNPs The improvement of impregnation of medical devices with silver nanoparticles is that it protects both outer and inner surfaces of medical devices and there is the continuous release of silver ions providing good antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%